A call to action: Managing the neural pathway of disgust, bias, prejudice, and discrimination that fuels stigma. Issue 4 (2nd October 2018) - Finnell, Deborah S.
Abstract: Stigma has long been cited as a barrier to individuals seeking treatment for alcohol and other drug use–related problems. This paper focuses on the foundation upon which stigma sits: the brain-based, neural and structural engine of prejudice and stereotyping, processes that lead to stigma. Research findings on the neural underpinnings of disgust, prejudice, bias, and discrimination are discussed. This commentary suggests the need to promote increased awareness of the neural drivers of stigma as a basis for managing responses to persons who use substances. The commentary challenges the use of the term "stigma, " calling for a new approach in lieu of foisting a badge of dishonor upon this population.